2015
DOI: 10.1109/tc.2014.2315617
|View full text |Cite
|
Sign up to set email alerts
|

SLA: A Stage-Level Latency Analysisfor Real-Time Communicationin a Pipelined Resource Model

Abstract: We present a communication analysis for hard real-time systems interconnects. The objective is to provide tight estimates on the worst-case communication latency between communicating processing elements that use a priority-aware communication medium for data transmission. The communication model consists of communication tasks transmitting data across a series of pipelined resources. The analysis incorporates interferences caused by multiple communication tasks requesting the pipelined resources, and it captu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 17 publications
0
26
0
Order By: Relevance
“…Targeting fixed-priority based NoCs, the authors in Burns (2008, 2009a, b) present a Response Time Analysis (RTA) based on the well-known analysis for task scheduling (Joseph and Pandya 1986). Kashif et al (2015) have proposed a stage-level latency analysis which can provide tighter estimates of latencies compared to the analysis presented in Shi and Burns (2008). However, the stage-level analysis is based on a condition that, the buffer at each router is large enough such that the transmission of a packet cannot be delayed because the buffer at a downstream router is full.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Targeting fixed-priority based NoCs, the authors in Burns (2008, 2009a, b) present a Response Time Analysis (RTA) based on the well-known analysis for task scheduling (Joseph and Pandya 1986). Kashif et al (2015) have proposed a stage-level latency analysis which can provide tighter estimates of latencies compared to the analysis presented in Shi and Burns (2008). However, the stage-level analysis is based on a condition that, the buffer at each router is large enough such that the transmission of a packet cannot be delayed because the buffer at a downstream router is full.…”
Section: Related Workmentioning
confidence: 99%
“…only holding several flits (Wentzlaff et al 2007;Baron 2010) which does not support the above condition. When the buffer size is not sufficient, the analysis in Kashif et al (2015) can produce optimistic results. Recently, the authors in Xiong et al (2016) have shown that the analysis of Shi and Burns (2008) can be optimistic when a NoC buffer can hold more than a single flit, and they proposed a new method to resolve the optimistic problem.…”
Section: Related Workmentioning
confidence: 99%
“…Also working on this topic, Shi and Burns [16] and Liu et al [17] derived methods for priority assignment, while Nikolić and Petters [18] introduced a novel arbitration policy and the accompanying worst-case analysis for flows with dynamic priorities. Kashif et al [19] proposed a stage level analysis which performs better than the traditional analysis, but requires sufficiently big buffers to store preempted flows.…”
Section: Related Workmentioning
confidence: 99%
“…Over the years, many analytical models of increasing complexity have attempted to calculate upper-bounds to the latency of packets injected in such a NoC [11], [7]. Those models make assumptions about the traffic generated by the realtime applications running on the NoC (e.g.…”
Section: Introductionmentioning
confidence: 99%